Perubahan Morfologi Kali Garang - Banjir Kanal Barat Tanpa Bendung Simongan (Pendekatan Model Simulasi BRI-STARS) - Edhisono, Soetarto (Department of Civil Engineering, Diponegoro University, 2006)
The changing of land-use on the upper Simongan Weir causes the increasing of flood discharge. It was shown during flood that occured on January 1990, which in that time flood water overtopped of the dikes and caused dikes collapsed in some places and flood was ocurred around Simongan area. This research was made because there was a plan to change the Simongan Weir into barrage, in order to make flood water level of the Garang River lower during flood. The crest of the Simongan Fixed Weir would be cutted in 3.7 m height in order to make flood water level lower, and to keep the water level remain the same during normal condition, some gates would be installed above the cutted weir crest as barrages. This situation would change river morphology of the Garang River and West Flood Way. This paper was contained simulation result of the changing of river morphology of the Garang River and West Flood Way without Simongan Weir by using BRI-STARS ( BRIdge Stream Tube model for Alluvial River Simulations ) software. This simulation model generated semi-two dimensional water flows and its sediment which capabled to compute scouring and silting on sub-critical, super critical flows and combination of these both flows conditions.Keywords: weir, barrage, morphology, scouring, siltationPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3950[How to cite: Edhisono, S., 2006, Perubahan Morfologi Kali Garang - Banjir Kanal Barat Tanpa Bendung Simongan (Pendekatan Model Simulasi BRI-STARS), Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 240-250]